Effects of group II elements on the cold stretch formability of Mg–Zn alloys. (15th January 2015) - Yuasa, Motohiro; Miyazawa, Naoki; Hayashi, Makoto; Mabuchi, Mamoru; Chino, Yasumasa
Abstract: Tensile tests and Erichsen tests were carried out at room temperature on Mg–Zn and Mg–Zn–X (X = Ca, Sr or Ba) alloys to investigate the effects of group II elements on cold stretch formability. First-principles calculations were also performed to understand the effects of group II elements on the basal and prismatic 〈a〉 slips. The flow stresses of the Mg–Zn–X alloys were lower than that of the Mg–Zn alloy. Furthermore, the addition of Ca, Sr or Ba enhanced the stretch formability of Mg–Zn alloys. The effectiveness for this enhanced stretch formability increased in order of decreasing atomic number of the group II elements. The enhanced stretch formability in the Mg–Zn–X alloys can be explained by calculations of the generalized stacking fault energy (GSFE). However, the difference in stretch formability between the Mg–Zn–Ba alloy and the Mg–Zn alloy could not be explained from the viewpoint of the GSFE. The stretch formability of Mg alloys is suggested to be related not only to thermally activated dislocation processes, but also to athermally activated processes.